KARAKTER FENOTIP DAN MOLEKULAR MELON (Cucumis melo L. âTACAPAâ) PADA MEDIA TANAM TANAH KARST - , Yuanita Rachmawati ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Yogyakarta district has 158.600 ha critical land and spread off in three Agro Ecosystem zones. Two of them are karsts critical land. Critical lands which contain calcium carbonate in high concentration and water dehydration in upper surface give abiotic stress in wide range of plant. Melon cultivar TACAPA has superior characteristic derived from parental crossing, â Action 434 and â PI 371795 and potential to be developed in karsts critical land. Abscicic acid (ABA) is a phytohormone expressed by plant in abiotic stress condition. CmBG1 is a gene which regulate ABA hormone in melon. The purposes of this research were examining the phenotipical and molecular characters of melon cultivar TACAPA in response to karsts critical land in order to study molecular characterization of CmBG1 gene. Analysis was done qualitatively by using Reverse Transcriptase- PCR (RT-PCR) and Electrophoresis, while quantitative analysis was conducted by observing absorbance score in spectrophotometer. CmBG1 gene expression is examined by using Real time PCR (qPCR). Result showed that almost morphological characters of melon such as plant height, amount of leaves, fruit weight and seed production have no significant differences with melon in control plantation media. Significantly difference results were showed in flowering time and water loss degree. Molecular characters obtained are CmBG1 detected in size Â±1258 bp, CmBG1 gene concentrations in melon which planted in control media are lower than melon in critical lands media. These results are similar with the real time quantitative analysis method. It also be revealed that melon TACAPA is more potential plant compared to another cultivar that can be developed in karst critical land area.